1961
DOI: 10.1161/01.res.9.2.333
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Ventricular Coronary Arteries in the Dog

Abstract: The ventricular coronary arterial system of the dog displays preponderance of the left in 100 per cent of the animals studied. The single most important source of blood supply is the left circumflex artery, which supplies not only most of the left ventricle, but also significant portions of the right ventricle. Details of the septal branch are described. Morphological implications concerning death or survival in experimental coronary occlusive procedures are discussed. A simple nomenclature is offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

1972
1972
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 8 publications
1
27
0
1
Order By: Relevance
“…Worthy of further investigations are the changes induced by the altered performance of the ischemic right ventricle on the left ven tricular function when ischemia is not ex tended to the septum. In the present investi gation, performed in the anesthetized dog in which, unlike what is observed in humans, the right coronary artery does not supply the sep tum [9], we studied the effect of regional right ventricular ischemia on the activity of the right ventricle and the effect of pure (without involvement of the septum) general right ven tricular ischemia on the activity of the right and left ventricles. after the occlusion, the loop is shifted towards the right showing an increase in ventricular dimensions; a re duced difference between the diastolic and the systolic area is also evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worthy of further investigations are the changes induced by the altered performance of the ischemic right ventricle on the left ven tricular function when ischemia is not ex tended to the septum. In the present investi gation, performed in the anesthetized dog in which, unlike what is observed in humans, the right coronary artery does not supply the sep tum [9], we studied the effect of regional right ventricular ischemia on the activity of the right ventricle and the effect of pure (without involvement of the septum) general right ven tricular ischemia on the activity of the right and left ventricles. after the occlusion, the loop is shifted towards the right showing an increase in ventricular dimensions; a re duced difference between the diastolic and the systolic area is also evident.…”
Section: Discussionmentioning
confidence: 99%
“…The dog was selected as an experimental model in which the left coronary artery is reported to supply at least one fourth of the margin of the right ventricle adjacent to the posterior longitudinal groove including the posterior part of the septum [9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have detailed the distribution of canine circumflex artery blood flow; major ischemia in the LV lateral and posterior walls and the posterior papillary muscle are produced by proximal circumflex coronary artery occlusion. 34,35 ED is often defined at the peak of the electrocardiographic R wave. We used the time of maximum volume to define ED and the ED reference dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…12 A number of studies have demonstrated the site of earliest activation of chronic human VT is normally in the subendocardium3-6 and that the majority of human VT is associated with infarcts extending into the interventricular septum.7-'6 Whereas the blood supply of the human interventricular septum arises from three to five large septal perforators that arise from the left anterior descending coronary artery, 75% of the canine interventricular septum receives its blood supply from a single artery, the anterior septal coronary artery. 17 To more closely mimic the anatomic substrate that gives rise to chronic VT in humans, we developed a canine model of chronic VT by creating ventricular septal Septal a.…”
mentioning
confidence: 99%